(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The work discusses the reforms being carried out in the professional education system in Uzbekistan and the specific aspects of increasing students’ interest in exact sciences, including mathematics, based on the module "Logarithmic function and its properties". The work presents some developments and methods related to the module.